FIXED DRUG ERUPTION OF THE EYELIDS. A DERMOSCOPIC EVALUATION - Manuel Valdebran; Rogelio Isao Salinas; Nelly Ramirez; Alba Rodriguez; Leyla Guzman; Silvia Marte; Max Suazo; Esmirna Rosado (Our Dermatology Online, 2013)
Fixed drug eruption (FDE) usually appears as a solitary or a small number of pruritic, well circumscribed, erythematous macules that evolve into edematous plaques; these lesions typically resolve after discontinuation of the offending drug, leaving hyperpigmentation at the site of lesions. Fixed drug eruption has been mentioned previously as a disease model for elucidating the mechanism of how skin inflammation is caused by skin-resident T cells, a multistep process that results in eventual tissue damage. In this article we discuss the utility of dermoscopy as an additional tool which gives significant information aiding us to infer these complex processes seen in FDE and thus to confirm the diagnosis